Field-Programmable Wiring Systems - Murray, Victor (2015)
Field-programmable wiring systems refer to methods and hardware that can maintain the interconnection of components of different types. Generally, field-programmable wiring systems support the use of multidomain fabrics that can be used to route analog, power, digital signals, optical, microwave signals, etc. This paper reviews fundamental concepts associated with the practical implementation of field-programmable wiring systems. The paper also provides different implementation examples and discusses a list of challenges and recommendations for future work in this area.